Reversal of Microalbuminuria A Causative Factor of Diabetic Nephropathy is Achieved with ACE Inhibitors than Strict Glycemic Control - R Tharakeswari, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Reversal of Microalbuminuria A Causative Factor of Diabetic Nephropathy is Achieved with ACE Inhibitors than Strict Glycemic Control